Transportasi Benih Ikan Nila (Oreochromis niloticus) Dengan Menggunakan Bahan Alami Ekstrak Lempuyang (Zingiber zerumbet) - Naim, Muhammad; Hardi, Esti Handayani; Warlina, Lina (Journal Galung Tropika, 2024)
Using natural anesthetic materials to transport tilapia fry is crucial for finding sustainable alternatives to commonly used chemicals. This study aims to demonstrate the effectiveness of lempuyang extract (Zingiber zerumbet) in transporting tilapia fry by increasing density and transportation duration while ensuring the well-being of the fry, as indicated by the survival rate. The study results suggest that Z. zerumbet can safely transport tilapia fry at a density of up to 145 fish/L, maintaining stable glucose levels and normal hematocrit. The survival rates remained consistently high at 99-100% with no significant differences. In conclusion, the study suggests that using Z. zerumbet at 5 mL/L in the transportation medium can support a density of 145 fish/L for up to 15 hours, making it an effective natural anesthetic for transporting fish fry.